2007
DOI: 10.1016/j.exer.2007.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Interocular agreement in melanin and macular pigment optical density

Abstract: Macular pigment (MP) and melanin possibly protect the macular area by absorbing blue light and acting as antioxidants. Because little is known about the interocular correlation of melanin, we determined its optical density (MOD) in both eyes of healthy subjects using fundus reflectometry. The measuring method also provided optical densities of MP (MPOD). In addition to evaluating its interocular correspondence we checked its dependency on central retinal thickness as measured with optical coherence tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
2
14
1
Order By: Relevance
“…20,21,27,28 However, consistent with our findings, Kanis et al recently measured MPOD by using fundus reflectometry and foveal thickness by using OCT in 37 subjects (36 of whom were white) and found that there was no significant linear association between MFT and MPOD (r ϭ 0.05, P ϭ 0.78) or between CFT and MPOD (r ϭ Ϫ0.04, P ϭ 0.82). 28 Aleman et al 21 measured inner retinal thickness in the central 1°by using OCT in a group of 49 patients (75 eyes) with retinitis pigmentosa (RP) or Usher syndrome (US) and 19 normal subjects (27 eyes) without ocular disease. They found that MPOD (at 0.5°, measured with HFP) was positively and significantly related to retinal thickness in the patient group (r ϭ 0.57, P Ͻ 0.001) and to a lesser extent in the normal subjects (r ϭ 0.39, P ϭ 0.12).…”
Section: Discussionsupporting
confidence: 90%
“…20,21,27,28 However, consistent with our findings, Kanis et al recently measured MPOD by using fundus reflectometry and foveal thickness by using OCT in 37 subjects (36 of whom were white) and found that there was no significant linear association between MFT and MPOD (r ϭ 0.05, P ϭ 0.78) or between CFT and MPOD (r ϭ Ϫ0.04, P ϭ 0.82). 28 Aleman et al 21 measured inner retinal thickness in the central 1°by using OCT in a group of 49 patients (75 eyes) with retinitis pigmentosa (RP) or Usher syndrome (US) and 19 normal subjects (27 eyes) without ocular disease. They found that MPOD (at 0.5°, measured with HFP) was positively and significantly related to retinal thickness in the patient group (r ϭ 0.57, P Ͻ 0.001) and to a lesser extent in the normal subjects (r ϭ 0.39, P ϭ 0.12).…”
Section: Discussionsupporting
confidence: 90%
“…Berendschot and van Norren [141] also used a newer version of the device, the FRA 2, which has a number of differences from the first version, including being smaller, which makes it desktop-mountable. Kanis et al [143,148] and van de Kraats and van Norren [139] have also used the FRA 2 in their studies.…”
Section: Fundus Camerasmentioning
confidence: 97%
“…Probably the most familiar optical model is that derived by van de Kraats, Berendschot and van Norren [140], which has been used to work out MPOD in several studies [e.g., 58,136,[141][142][143][144]. In essence, the density of macular pigment is determined using its known spectral characteristics, and by taking into account the amount of light reflected at the internal limiting membrane, the photoreceptor discs and the sclera [58,136,140,141,143]. The densities of the lens, melanin and blood are likewise calculated.…”
Section: Fundus Reflectometrymentioning
confidence: 99%
“…A number of studies report considerable symmetry in the central retinal features of the fellow eyes in normal subjects, including central cone photoreceptor density evaluated with adaptive optics, 31,32 optical coherence tomography measures of macular thickness, 33 macular pigment density, 34,35 and macular blood flow. 36 In light of these data, one could speculate that under the action of common mechanistic noxious determinants (such as genetic mutations, environmental and systemic factors), the likelihood of photoreceptor dysfunction and loss would have a similar retinal distribution in the two eyes of a patient, eventually resulting in bilateral symmetry of functional visual loss.…”
Section: Discussionmentioning
confidence: 99%